A simple hope : a Lancaster Crossroads novel - Lauer, Rosalind (New York : Ballantine Books Trade Paperbacks, 2014)
Confined to a wheelchair, James Lapp's unwilling to saddle Rachel King with his troubles, but a runaway Englisher girl unites them in a common goal.
Keywords: Amish -- Fiction; Accidents -- Fiction; Paralytics -- Fiction; Fathers and sons -- Fiction; Man-woman relationships -- Fiction; Runaway children -- Fiction; Life change events -- Fiction; Christian fiction; Love stories